Rasprostranenie sufizma v Kitae: religiovedčeskij analiz - Adiljan, G. (Chabaršy. Dintanu serijasy, 2023)
In the scientific article about the features of the polytheists, Sufis can be described as devout Muslims: five-time prayer, fasting and etc. However, they are unique in fostering the spiritual dimension of themselves and others. They know that one of the names of the Prophet is "Dhikr Allah" (remembrance of Allah). The most important Buddhism of the People’s Republic of China, focusing on the post-Christian religion of Islam, provides extensive information on the Sufi direction within it. The features of the current state and spread of Sufism, as well as the history and influence of Sufi Justice introduced into China, allow readers to gradually understand the influence of Islamic support for Sufism on Islam in China. Except for Sufi followers, there are many Muslims from different minority groups, and in the way they believe in Islam or Islamic sects, they also choose with great varieties. For the study of the relationship between Islam and Sufism in China, especially the influence of Sufism on Islam in the Central Plain, Sufism in China has gained real value. Not only in the field of thought, but also in the field of Muslim cognition. The activity of the Sufi movement has spread throughout the Islamic world and is still active in Islamic countries and regions. The ideology of Sufism has a certain influence on the religious and social life of Muslims.